Monitoring geodynamic activity in the Victoria Land, East Antarctica: Evidence from GNSS measurements - A. Zanutta; M. Negusini; L. Vittuari; Paola Cianfarra; Francesco Salvini; F. Mancini; P. Sterzai; M. Dubbini; A. Galeandro; A. Capra (Journal of Geodynamics, 2017)
GNSS networks in Antarctica are a fundamental tool to define actual crustal displacements due to geological and geophysical processes and to constrain the glacial isostatic models (GIA). A large network devoted to the detection and monitoring of crustal deformations in the Northern Victoria Land (Victoria Land Network for DEFormation control – VLNDEF), was monumented during the 1999–2000 and 2000–2001 field campaigns, as part of Italian National Program for Antarctic Research and surveyed periodically during the Southern summer seasons. In this paper, GPS observations of VLNDEF collected over a more than 15-year span, together with various selected POLENET sites and more than 70 IGS stations, were processed with Bernese Software, using a classical double difference approach. A solution was obtained combining NEQs by means of ADDNEQ2/FODITS tools embedded in Bernese Software. All the Antarctic sites were kept free and a subset of 50 IGS stations were used to frame VLNDEF into ITRF2008. New evidence provided by analysis of GPS time series for the VLNDEF network is presented; also displacements along the vertical component are compared with the recently published GIA models. The absolute velocities indicate an overall displacement of the northern Victoria Land region along the south-east direction (Ve=10.6 mm/yr, Vn =−11.5 mm/yr) and an average uplift rate of Vu =0.5 mm/yr. Two GIA models have been analyzed: ICE-6G_C-VM5a proposed by Argus et al. (2014), Peltier et al. (2015) and W12A_v1 by Whitehouse et al. (2012a,b). Up rates, predicted over the VLNDEF sites by the mentioned GIA models, have been extracted and compared with those observed. A preliminary comparison with GPS-derived vertical rates shows that the Victoria Land ICE-6G_C-VM5 and W12A_v1 GIA models predict overestimated uplift rates of 0.7 and 0.9 mm/yr weighted mean residuals respectively. The mean horizontal relative motions within the Victoria Land (VL) area are in most cases negligible, while only a few points exhibit horizontal velocities greater ...